Biallelic mutations in the ferredoxin reductase gene cause novel mitochondriopathy with optic atrophy. (5th October 2017) - Peng, Yanyan; Shinde, Deepali N; Valencia, C Alexander; Mo, Jun-Song; Rosenfeld, Jill; Truitt Cho, Megan; Chamberlin, Adam; Li, Zhuo; Liu, Jie; Gui, Baoheng; Brockhage, Rachel; Basinger, Alice; et al.
Abstract: Iron–sulfur (Fe-S) clusters are ubiquitous cofactors essential to various cellular processes, including mitochondrial respiration, DNA repair, and iron homeostasis. A steadily increasing number of disorders are being associated with disrupted biogenesis of Fe–S clusters. Here, we conducted whole-exome sequencing of patients with optic atrophy and other neurological signs of mitochondriopathy and identified 17 individuals from 13 unrelated families with recessive mutations in FDXR, encoding the mitochondrial membrane-associated flavoprotein ferrodoxin reductase required for electron transport from NADPH to cytochrome P450. In vitro enzymatic assays in patient fibroblast cells showed deficient ferredoxin NADP reductase activity and mitochondrial dysfunction evidenced by low oxygen consumption rates (OCRs), complex activities, ATP production and increased reactive oxygen species (ROS). Such defects were rescued by overexpression of wild-type FDXR . Moreover, we found that mice carrying a spontaneous mutation allelic to the most common mutation found in patients displayed progressive gait abnormalities and vision loss, in addition to biochemical defects consistent with the major clinical features of the disease. Taken together, these data provide the first demonstration that germline, hypomorphic mutations in FDXR cause a novel mitochondriopathy and optic atrophy in humans.